2021
DOI: 10.1096/fj.202100353r
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic cataract in the Nile grass rat: A longitudinal phenotypic study of pathology formation

Abstract: Diabetes is a major risk factor for cataract, the leading cause of blindness worldwide.There is an unmet need for a realistic model of diabetic cataract for mechanistic and longitudinal studies, as existing models do not reflect key aspects of the complex human disease. Here, we introduce and characterize diabetic cataract in the Nile grass rat (NGR, Arvicanthis niloticus), an established model of metabolic syndrome and type 2 diabetes (T2D). We conducted a longitudinal study of cataract in over 88 NGRs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…Importantly, house mouse and Norway rat are relatively resistant to diet-alone induced diabetes, modeling pre-diabetes or early-diabetes and unable to develop long-term diabetic complications [14,15]. Conversely, Nile rats on rodent chow, without chemical or genetic manipulations, recapitulate the natural progression of type 2 diabetes in humans [16] including clinically relevant diabetic complications [17][18][19]. Notably, the diurnal Nile rat has a cone-rich retina that is useful to study human retinal diseases, including diabetic retinopathy.…”
Section: Open Accessmentioning
confidence: 99%
“…Importantly, house mouse and Norway rat are relatively resistant to diet-alone induced diabetes, modeling pre-diabetes or early-diabetes and unable to develop long-term diabetic complications [14,15]. Conversely, Nile rats on rodent chow, without chemical or genetic manipulations, recapitulate the natural progression of type 2 diabetes in humans [16] including clinically relevant diabetic complications [17][18][19]. Notably, the diurnal Nile rat has a cone-rich retina that is useful to study human retinal diseases, including diabetic retinopathy.…”
Section: Open Accessmentioning
confidence: 99%
“…Эти животные являются ценной спонтанной моделью для исследований, направленных на предотвращение диабета, вызванного пищевым рационом, и представляют собой новую систему взаимодействий между генами и рационом, влияющую на использование энергии. Эта модель позволит лучше понять подходы к профилактике и лечению СД2 и метаболического синдрома [97][98][99][100][101].…”
Section: модели с индуцированным ожирениемunclassified
“…These animals are a valuable spontaneous model for research aimed at preventing diet-induced diabetes and represent a novel system of the interactions between genes and diet that affect energy use. This model will allow for a better understanding of the approaches to prevent and treat T2DM and the metabolic syndrome [ 97 , 98 , 99 , 100 , 101 ].…”
Section: Genetic Models With Obesitymentioning
confidence: 99%
“…Recently, we introduced a novel diabetic cataract model in the Nile grass rat (NGR, Arvicanthis niloticus ) [ 4 ], a diurnal gerbil that naturally develops metabolic syndrome (MetS) and T2D [ 5 , 6 ]. Our study revealed spontaneous formations of diverse cataract types, including the posterior sub-capsular (PSC), cortical, nuclear, and anterior sub-capsular (ASC) cataracts, all of which temporally succeeded hyper-reflective early dot-like microlesions in the equatorial regions [ 4 ]. These early lesions reminisce of supranuclear cataracts in Alzheimer’s disease [ 7 ], or blue-dot opacities in pediatric cataract [ 8 ], and in individuals with Down syndrome [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the role of LECs and immune cells in diabetic cataract formation. We reported LEC proliferation and migration in early diabetic cataract [ 4 ]. Here, we explore a novel role for immune cells in this cellular reprogramming.…”
Section: Introductionmentioning
confidence: 99%